THE POINT OF VIEW YOUTH TOURISM TOWARDS UNIVERSITY STUDENTS - Kilili, Rukiye; CİZRELİOĞULLARI, Mehmet Necati; Altun, Özlem (The journal of contemporary issues in business and government, 2021)
The main purpose of the present study is to investigate the point of view of youth tourism towards university students. In this context, it examines the perspectives of students from the age of 18 to the age of 27 studying in Cyprus Science University andDicle University on youth tourism to determine the factors affecting the preferences of young people.SPPS 24 and AMOS 24 statistical programs were used.A total of 323 questionnaires was collected. In line with the results of the opinions of 135 private university students and 188 public university students who answered the questions in the questionnaire, it is seen that young individuals are directly affected by economic, accommodation, transportation and security factors when they are making holiday plans.Also, it was concluded that the gender variable have a direct effect on perceptions and views of university students towards youth tourism.